Analisis Loyalitas Pelanggan Dalam Penggunaan Dompet Digital Dana - Yeni Lasmawati; Zanuba Qotrun Nada; Syamsul Hidayat (BADAN PENERBIT STIEPARI PRESS, 2024)
E-wallet or digital wallet is a form of payment technology that allows users to store, send and receive money digitally. The aim of this research is to find out whether service quality and customer satisfaction can influence customer loyalty in using the DANA digital wallet. The population in this study were people who had used the DANA digital wallet application with a sample size of 150 respondents. Data was obtained by distributing questionnaires via a Google Form link. The method used in this research is a quantitative method with data analysis techniques used including data normality test, heteroscedasticity test, multicollinearity test, validity and reliability test, and multiple regression test. From the research results, it was found that e-service quality has an effect on customer loyalty, customer satisfaction has no effect on customer loyalty and e-service quality and customer satisfaction together have an effect on customer loyalty.